Síndrome de Burnout y su relación con la inteligencia emocional en los servidores del GAD Junín periodo diciembre 2021 junio 2022 - Marcillo López, Jessica Valeria (2023)
The present research work was carried out with the purpose of evaluating Burnout syndrome and its relationship with emotional intelligence in public servants of the Junín cantonal GAD period December 2021 June 2022 for the improvement of work performance, in which economic, social and legal theories were investigated, which helped to support the investigation. In the same sense, methods such as inductive, deductive and analytical were used, which contributed to the development of the activities, while the research techniques used helped to gather information, which were; the survey addressed to public servants, in which the Excel tool was used to tabulate the results obtained, while the interviews were applied to the departmental directors of the GAD and resulted in the presence of moderate levels of stress in two of them. The evaluated addresses also frequently present headaches and muscle ailments in the evaluated officials, in addition there are moderate levels of physical and mental exhaustion on the part of public servants. Finally, the conclusions of the investigation determined that the GAD of Junín must plan institutional policies that allow the reduction of work stress and mitigate the factors that promote the appearance of Burnout syndrome, they must also use habitual evaluations in relation to work stress.